Former Yugoslav Republic of Macedonia : Fourth Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES The jobs and growth agenda should remain a top policy priority, with efforts focused on relaxing key constraints for domestic firms. Priorities include properly implementing and monitoring recent initiatives to enforce payment discipline in both public and private sector contracts, as well as upgrading the professional status of inspection bodies, clarifying their mandate, and streamlining their work. The public-sector led growth strategy will put pressure on other types of spending if consolidation is to proceed in the current low-tax environment. Investment spending should target gaps in transport and energy infrastructure to maximize the payoff for medium-term growth. At the same time, with public debt rising steadily to over 50 percent of GDP by 2017, fiscal policy should aim at reducing the deficit to below 2.6 percent of GDP by 2016. In the absence of further tax policy changes to boost revenues, a comprehensive spending review that seeks to minimize the growth impact of current expenditure compression should therefore be undertaken. More comprehensive public debt management is needed to support external sustainability. To further reduce risks, particularly currency risk, the strategy should be expanded to cover the debt of SOEs and contingent liabilities. Increased reliance on foreign currency borrowing also has important implications for central bank reserve developments and domestic liquidity that should be taken into account in evaluating government financing options. The monetary easing cycle has reached its end. The combination of relaxed financial conditions and tight prudential regulation has helped revive credit growth while preserving the health of the financial sector. While temporary supply-side developments have recently generated deflationary pressures, the focus of monetary policy henceforth should be on maintaining the attractiveness of holding denar-denominated assets in support of the exchange rate peg. Outstanding credit is scheduled to fall below 200 percent of quota at end-year. The external position and capacity to pay are sufficiently strong to allow for a cessation of post-program monitoring.